The Role of a Nurse in Conducting Peritoneal Dialysis for Chronic Renal Failure in Children - Аnastasiya М. Milovanova (Педиатрическая фармакология, 2017)
Replacement renal therapy is the only method for treating the terminal stage of chronic renal failure before kidney transplantation, if such one is possible. In recent years, the frequency of outpatient peritoneal dialysis, conducted both in a hospital and at home, has increased for this purpose in children. The efficacy of dialysis and minimization of complications, especially peritonitis, depend not only on the program chosen by a doctor but also on the correct execution of the procedure and the observance of aseptic and antiseptic rules by persons performing dialysis (nurse and mother). The article introduces the basic principles of dialysis: demonstrating the role of a nurse in the procedure, the author justifies the need to improve knowledge in the field of renal replacement therapy in order to intelligently and easily explain the essence of dialysis to a mother and teach her how to perform the procedure independently.